Hypogonadism in Exercising Males: Dysfunction or Adaptive-Regulatory Adjustment? - Hackney, Anthony C. (Frontiers in Endocrinology, 2020)
For decades researchers have reported men who engaged in intensive exercise training can develop low resting testosterone levels, alterations in their hypothalamic-pituitary-gonadal (HPG) axis, and display hypogonadism. Recently there is renewed interest in this topic since the International Olympic Committee (IOC) Medical Commission coined the term ‘Relative Energy Deficiency in Sports’ (RED-S) as clinical terminology to address both the female-male occurrences of reproductive system health disruptions associated with exercise. This IOC Commission action attempted to move beyond the sex-specific terminology of the "Female Athlete Triad" (Triad) and heighten awareness/realization that some athletic men do have reproductive related physiologic disturbances such as lowered sex hormone levels, HPG regulatory axis alterations, and low bone mineral density similar to Triad women. There are elements in the development and symptomology of exercise-related male hypogonadism that mirror closely that of women experiencing the Triad/RED-S, but evidence also exists that dissimilarities exist between the sexes on this issue. Our research group postulates that the inconsistency and differences in the male findings in relation to women with Triad/RED-S are not just due to sex dimorphism, but that there are varying forms of exercise-related reproductive disruptions existing in athletic men resulting in them displaying a relative hypogonadism condition. Specifically, such conditions in men may derive acutely and be associated with low energy availability (Triad/RED-S) or excessive training load (overtraining) and appear transient in nature, and resolve with appropriate clinical interventions. However, manifestations of a more chronic based hypogonadism that persists on a more permanent basis (years) exist and is termed the ‘Exercise Hypogonadal Male Condition’. This article presents an up-to-date overview of the various types of acute and chronic relative hypogonadism found in athletic men and proposes mechanistic models of how these various forms of exercise relative hypogonadism develop.